2015
DOI: 10.1080/15504263.2014.992588
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Acceptance and Commitment Therapy Smoking Cessation Treatment for Smokers With Depressive Symptoms

Abstract: Objective Smokers with depressive symptoms have more difficulty quitting smoking than the general population of smokers. The present study examines a web-based treatment using Acceptance and Commitment Therapy (ACT) for smokers with depressive symptoms. The study aimed to determine participant receptivity to the intervention and its effects on smoking cessation, acceptance of internal cues, and depressive symptoms. Methods Smokers who screened positive for depressive symptoms at baseline (n = 94) were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 27 publications
(28 reference statements)
1
49
0
Order By: Relevance
“…The results of the present pilot feasibility study suggest that: (i) it is feasible to recruit and retain smokers with stable bipolar disorder in a smoking cessation study; and (ii) ACT is highly acceptable to smokers with bipolar disorder, shows promising effects on smoking abstinence, and appears to impact its theory‐based mechanism of action for smoking cessation (i.e., acceptance). These findings are consistent with previous work demonstrating ACT's preliminary acceptability and efficacy in broader general population samples of smokers as well as among smokers with current depressive symptoms . The observed increase in acceptance is similar to our prior work, where a 50% increase in AIS scores from baseline to post‐treatment was associated with a 51% increase in the odds of quitting [odds ratios = 1.51, 95% confidence interval: 0.37–6.23; unpublished results from ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present pilot feasibility study suggest that: (i) it is feasible to recruit and retain smokers with stable bipolar disorder in a smoking cessation study; and (ii) ACT is highly acceptable to smokers with bipolar disorder, shows promising effects on smoking abstinence, and appears to impact its theory‐based mechanism of action for smoking cessation (i.e., acceptance). These findings are consistent with previous work demonstrating ACT's preliminary acceptability and efficacy in broader general population samples of smokers as well as among smokers with current depressive symptoms . The observed increase in acceptance is similar to our prior work, where a 50% increase in AIS scores from baseline to post‐treatment was associated with a 51% increase in the odds of quitting [odds ratios = 1.51, 95% confidence interval: 0.37–6.23; unpublished results from ].…”
Section: Discussionsupporting
confidence: 91%
“…All participants were self-selected. Of the participants, 2 RCTs were recruited from a clinical population (pain clinics) [ 49 , 50 ], 2 from an undergraduate student population [ 47 , 48 ] whereas the remainder were recruited from the general population [ 29 , 36 , 45 , 46 , 51 ]. Trials ranged in size from 38 to 236 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Powers et al [ 24 ] reported a “clear effect and overall advantage of ACT compared to control conditions” but found no evidence to suggest it was more effective than established treatments. Others have also reported ACT to be effective across a range of conditions, including psychiatric disorders [ 25 ], chronic pain [ 26 - 28 ], tinnitus [ 29 ], multiple sclerosis [ 30 ], anxiety disorders [ 31 , 32 ], stress [ 33 - 35 ], and health behavior or lifestyle change together with smoking [ 36 - 39 ] and weight optimization [ 40 ]. Thus whilst there is some uncertainty of the effectiveness of ACT, it appears to be related more to establishing the evidence base rather than ACT being an ineffective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The studies where the target behaviours were not changed were also unsuccessful in altering depressive symptoms (Geisner et al, 2015;Jones et al, 2015;Schaub et al, 2012). This may be because substance abuse and smoking cessation are more resistant to change in a depressed population (Jones et al, 2015;Schaub et al, 2012), or perhaps, more likely, the lack of change was due to deficits in elements of the intervention design and small sample sizes. In support of this, while no significant results were achieved, Jones et al (2015) reported positive trends in both depressive symptoms and smoking cessation in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the implementation techniques are driven by the theoretical framework the intervention is based on, as opposed to the target audience. Jones et al (2015) discussed the theoretical approach used in their intervention and how it might be beneficial for depressed populations in their analysis, but not specific intervention features. In addition, their study was a post hoc analysis of a depressed subset and not an intervention specifically designed for depressed populations.…”
Section: Australian and New Zealand Journal Of Psychiatry 52(9)mentioning
confidence: 99%